Quercetin protect cigarette smoke extracts induced inflammation and apoptosis in RPE cells - Qi Zhu; Mingxi Liu; Yuxi He; Bo Yang (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Background Age-related macular degeneration (AMD) is the leading cause of blindness in elderly population in the developed world. Dysfunction of retinal pigment epithelium (RPE) likely triggers early AMD stages. The effect of Quercetin on the early AMD in-vitro model remained unclear.Methods The effect of Quercetin in the cell viability was detected with CCK8 methods in control, CSE treated, and CSE with Quercetin treatment group. The apoptotic status in each group was detected with tunnel assay. The oxidative and inflammation biomarkers were detected by ELISA. The expression levels of Keap1/Nrf2/ARE in RPE cells were measured by western blot after pretreatment of Quercetin followed by CSE treatment.Results It was found that Quercetin could improve the cell viability and decrease cellular apoptotic rate in the CSE treated RPE group. The expressions of inflammatory and apoptotic biomarkers were significantly decreased in Quercetin treatment group. Furthermore, Quercetin exerts protective effects via activation Keap1/Nrf2/ARE pathway in CSE treated RPE cells.Conclusions Quercetin demonstrated significant protective effects in an in-vitro model of early AMD and it might be a new therapeutic strategy for the management of early AMD.